The effects of fertilization regime on growth parameters and bioactive properties of pot grown Cichorium spinosum L. - Polyzos, Nikolaos (2022)
Cichorium spinosum L. is a wild edible species found mostly in coastal areas of the Medi-terranean basin. In this experiment, seven fertilization treatments varying in the amounts of N:P:K were applied via nutrient solution feeding in pot-grown C. spinosum plants, namely 100:100:100 (C111), 200:100:100 (C211), 200:200:200 (C222), 300:100:100 (C311), 300:200:200 (C322) and 300:300:300 (C333) ppm ratio of N:P:K and control where no fertilizers were added (C0). The growth parameters tested included the number and the fresh and dry weight of leaves, SPAD index, leaf area index (LAI) and specific leaf area (SLA). Bioactive parameters, including the antioxidant (OxHLIA and TBARS assays), anti-inflammatory (RAW 264.7 cell line) and cytotoxic (PLP2, AGS, CaCo2, VERO and MCF7 cell lines) were examined in aqueous and hydroethanolic extracts of leaves. Fertilizer treatments benefited the growth parameters of spiny chicory, while the highest antioxidant activity was recorded for the C222 and C311 treatments. The application of fertilizers on C. spinosum plants had positive effects on plant growth, chemical composition and bioactive properties.